Penerapan Media Permainan Sosiology Shot Traditional (SOSIS –T) untuk Meningkatkan Motivasi Belajar Sosiologi Siswa MAN 1 Lombok Timur - Siti Surodiana (Jurnal Paedagogy, 2020)
This study aims to increase student motivation in sociology subjects through the application of the Sosis-T game media. This research method used classroom action research methods with research subjects namely students of class XII IPS 2 MAN 1 East Lombok. The research instrument used observation and tests. The research data were analyzed using descriptive qualitative and quantitative techniques. The results showed that the learning media Sosiology Shot Traditional (SOSIS-T) was more effective in increasing the learning motivation and grades of students in the classroom. Through the application of the Sosiology Shot Traditional (SOSIS-T) media it is very fun for students when used during learning. Students are very motivated and enthusiastic to follow it. Students actively move, ask, answer, and respond so that class conditions become more dynamic.